Review of the Rice Field Profit Sharing System (Muzara’ah) in Sei Siarti Village, Panai Tengah District, Labuhan Batu - Siregar, Sri Indah; Anggraini, Tuti; Harahap, Muhammad Ikhsan (Jurnal Bisnis dan Manajemen, 2025)
To examine how the profit sharing (muzara’ah) is reviewed which is called ballek dame by the sei siarti community. This research uses a qualitative approach with descriptive analysis techniques. According to Moleong (2021), qualitative research is research that aims to understand the phenomena experienced by research subjects holistically by describing them in the form of words and language, in a special, natural context.Data analysis was carried out using a qualitative descriptive analysis method through data reduction, data presentation and drawing conclusions as stated by Miles and Huberman in Suryani (2020) .Management of rice fields using the ballek dame system is a form of cooperation between land owners and land managers. Ballek dame has a term, namely Bebun which refers to the part of the harvest that is the right of the cultivating farmer, while pasrahan is the part of the harvest that is the right of the rice field owner. In this research, the land owner contributes to providing arable land, seeds, fertilizer and tools for cultivating the land, while the manager is responsible for all forms of land management. The share of agricultural products is relatively equal for each land owner and land manager, with a ratio of 4:1, where 4 parts are for the land owner and 1 part is for the land manager.This division reflects the recognition that the landowner provides the high-risk, high-value underlying asset, while the manager provides labor and management sevices. He ballek dame system which is based on the muzara’ah system in its application in the Sei Siarti village is running fairly, however there is no recording and contracts that are only verbal are feared to have bad potential in the future.